Preventing iron(ii) precipitation in aqueous systems using polyacrylic acid: some molecular insights. Issue 26 (22nd June 2018) - Artola, Pierre-Arnaud; Rousseau, Bernard; Clavaguéra, Carine; Roy, Marion; You, Dominique; Plancque, Gabriel
Abstract : We show that molecular simulations are able to describe iron(ii ) complexation by polyacrylic acid, thus preventing oxide precipitation in the secondary coolant circuit of nuclear power plant. Complexation is favoured with increasing polymer chain length. Abstract : We present molecular dynamics simulations of aqueous iron(ii ) systems in the presence of polyacrylic acid (PAA) under the extreme conditions that take place in the secondary coolant circuit of a nuclear power plant. The aim of this work is to understand how the oligomer can prevent iron(ii ) deposits, and to provide molecular interpretation. We show how, to this end, not only the complexant ability is necessary, but also the chain length compared to iron(ii ) concentration. When the chain is long enough, a hyper-complexation phenomenon occurs that can explain the specific capacity of the polymer to prevent iron(ii ) precipitation.